White matter degeneration revealed by fiber‐specific analysis relates to recovery of hand function after stroke. Issue 16 (18th August 2021) - Cheng, Bastian; Petersen, Marvin; Schulz, Robert; Boenstrup, Marlene; Krawinkel, Lutz; Gerloff, Christian; Thomalla, Götz
Abstract: Recent developments of higher‐order diffusion‐weighted imaging models have enabled the estimation of specific white matter fiber populations within a voxel, addressing limitations of traditional imaging markers of white matter integrity. We applied fixel based analysis (FBA) to investigate the evolution of fiber‐specific white matter changes in a prospective study of stroke patients and upper limb motor deficit over 1 year after stroke. We studied differences in fiber density and macrostructural changes in fiber cross‐section. Motor function was assessed by grip strength. We conducted a whole‐brain analysis of fixel metrics and predefined corticospinal tract (CST) region of interest in relation to changes in motor functions. In 30 stroke patients (mean age 62.3 years, SD ±16.9; median NIHSS 4, IQR 2–5), whole‐brain FBA revealed progressing loss of fiber density and cross‐section in the ipsilesional corticospinal tract and long‐range fiber tracts such as the superior longitudinal fascicle and trans‐callosal tracts extending towards contralesional white matter tracts. Lower FBA metrics measured at the brainstem section of the CST 1 month after stroke were significantly associated with lower grip strength 3 months ( p  = .009, adjusted R 2  = 0.259) and 1 year (T4: p  < .001, adj. R 2  = 0.515) after stroke. Compared to FA, FBA metrics showed a comparably strong association with grip strength at later time points. Using FBA, we demonstrate progressive fiber‐specific white matter loss after stroke and association with functional motor outcome. Our results promote the application of fiber‐specific analysis to detect secondary neurodegeneration after stroke in relation to clinical recovery. Abstract : Using Fixel based analysis, we demonstrate progressive fiber‐specific white matter loss after stroke and association with functional motor outcome. Our results promote the application of fiber‐specific analysis to detect secondary neurodegeneration after stroke in relation to clinical recovery.